Epidemiological characteristics and survival analysis on patients with occupational pneumoconiosis in Zhejiang Province from 1987 to 2019 - Zou, Hua; Shi, Zhihao; Zhang, Yixin; Zhou, Jiena; Fang, Xinglin; Zhang, Yijin; Hu, Yong; Lou, Xiaoming; Zhou, Lifang (Frontiers in Public Health, 2022)
Objective To evaluate risk factors affecting survival in patients diagnosed with pneumoconiosis and propose strategies to improve the quality of life in these patients. Methods The basic patient information was obtained from the pneumoconiosis report card. Disease types, regions, and industry distribution of pneumoconiosis were analyzed. The Kaplan-Meier survival curves and the Cox proportional risk regression model was used for survival analysis. Results A total of 13,812 patients were diagnosed with pneumoconiosis in Zhejiang province from 1987 to 2019. The overall survival rate at the end of life table analysis was 83%. Kaplan-Meier analyses showed that there were significant differences between survival curves depending on the stage of first diagnosis, age at first diagnosis, type of pneumoconiosis, industry, and duration of dust exposure (P < 0.05). The results of Cox proportional hazards regression analysis showed that pneumoconiosis stage of first diagnosis, age at first diagnosis, industry, and duration of dust exposure were risk factors affecting patient survival (P < 0.05). Conclusions The patients with high stage of pneumoconiosis at first diagnosis, older age, and long duration of dust exposure should be followed up and monitored as key population, and the industries with high incidence of pneumoconiosis such as mining and construction should be supervised as key industries.